Marigold garden : pictures and rhymes - Greenaway, Kate, 1846-1901. (London ; New York : F. Warne, 1900)
A collection of illustrated poems about the various activities of childhood.
Engraved, illustrated t.p. and half t.p.
First published in 1885.
Keywords: Greenaway, Kate, -- 1846-1901.; Children's poetry, English; English poetry